Advances in Helper-Dependent Adenoviral Vector Research - Segura, Maria M.; Alba, Raul; Bosch, Assumpcio; Chillon, Miguel (Current Gene Therapy, 2008)
The immunogenicity and cytotoxicity associated with early generations of adenoviral vectors provided a strong incentive for the development of helper-dependent adenovirus, a last generation of adenoviral vectors that is devoid of all viral coding sequences. These vectors have shown to mediate longer high-level transgene expression in vivo with reduced toxicity and thus offer enormous potential for human gene therapy. In addition, they possess a considerably larger cloning capacity than conventional adenoviral vectors making the transfer of large cDNAs, multiple transgenes and longer tissuespecific or regulable promoters possible. In this article, we review the progress made with helper-dependent adenoviral vectors. The development and optimization of scalable production processes and strategies for helper removal will be presented. Current chromatography options available for vector purification and the new challenges facing researchers for the separation of empty particles and/or helper viruses will be discussed. Finally, we will describe recent advances made in our understanding of their interaction with the immune system and their potential as gene delivery vehicles in vivo for the treatment of diseases affecting liver, skeletal muscle and brain.
Keywords: Gutless adenoviral vectors